Stereoscopy as a specific tool of advanced industrial engineering: monograph - Gašo, Martin (Advanced industrial engineering, 2025)
This monograph represents a complex overview of stereoscopic application issues as an advanced tool of industrial engineering. First part describes stereoscopic principles, and second part describes creation regulation of stereoscopic recording in converging camera axes setting. This description is based on its own math model that was designed for research at the Department of Industrial Engineering in Zilina. The core of this chapter describes creation methodology of stereoscopic recordings in Industrial Engineering. The main core of presented methodology is protected by the utility model, registration No SK 7683 Y1